Governing freedom through risk: locating the group home in the archipelago of confinement and control - Spivakovsky, Claire (Punishment & society, 2017)
This article seeks to enhance criminology’s understanding of the disability group home as a targeted site for confining and regulating disabled bodies. In particular, it seeks to extend criminology’s burgeoning understanding of the archipelago of confinement and control, and build upon others’ observations that within this archipelago, the penal has become mobile through site, and the carceral mobile through (disabled) body. The article shows how group homes serve a dual purpose and are marked by an uneven, bifurcated practice. For the vast majority of residents, group homes share little in common with other sites of confinement, but for a select few they can become multilayered sites of confinement and control, containing people first through the site of the group home itself, and then through the site of the person’s disabled body (with all that the designation of disability permits under law). Data supporting the analysis are drawn from the Australian state of Victoria and includes both government documents, as well as transcripts from interviews with 12 stakeholders who provide services and support to people with disability residing within group homes.